MEWUJUDKAN DESA SEHAT: UPAYA MENSEJAHTERAKAN MASYARAKAT - Sakdiyah, Khofifatus; Salahudin (MAJAPAHIT POLICY, 2022)
According to the Big Indonesian Dictionary, the meaning of prosperous is peaceful, happy, and healthy. So that a prosperous society is a society that is healthy, peaceful, and happy. A prosperous life is marked by a reduction in dangerous and infectious diseases, people live in a more friendly and green environmental area. In addition, it has healthy environmental and housing facilities, and always has partners in maintaining sustainability. A prosperous society can be realized if the population is able to participate in development. So development strategies and efforts should aim to improve society. The Healthy Village program is a movement to empower potential residents and village community groups to create a healthy family and environment. Village community empowerment is an effort to develop community independence and welfare by increasing knowledge, attitudes, skills, behavior, and utilizing resources through the establishment of policies, programs, activities, and assistance in accordance with the essence of the problem and priority needs of the village community. Realizing a "Healthy Village" requires total community participation, while health service institutions or institutions are only a motivator or guide in public health efforts. The role of rural communities in the health sector must be realized in an effort to encourage every individual, family and/or community institution including the private sector to take responsibility for the health of themselves, their families and communities.